Ketika Dakwah Bertemu Teknologi Ikhtiar Menjaga Akal Sehat Di Era Digital - Lismawati Lismawati; Masduki Asbari; Hikmatis Jum'a; Yulia Wulandari (Journal of Information Systems and Management (JISMA), 2025)
knowledge in the 9th century in Baghdad. This report is based on an oral story from the Gita Wirjawan channel entitled "Habib Husein Ja'far: Akal yang Salih dan Sosial, Bukan Hanya Ritual." The results of this study indicate that defending religion must be done with sincerity from the heart. In today's digital era, much can be done and distinguished in the process of preaching. This study is rooted in Islamic history, where maintaining religion is very important and can be done in various ways, including digitally, such as through social media. On this platform, there are many concepts that can change a person's perspective on their religious beliefs by using reason, especially in the community. The digital era has brought major changes in various aspects of life, including the way religion is practiced and spread. The purpose of this study is to explore the role of digitalization of religion in maintaining rationality and individual mental health in the digital era. With a qualitative-descriptive methodology, this study explains how digital media can function as a convenient, logical, and appropriate religious education tool. The research findings show that the digitalization of religion can act as a moral defense as well as a filter for positive information, as long as it has adequate digital literacy support.